2007
DOI: 10.1159/000101544
|View full text |Cite
|
Sign up to set email alerts
|

Distortion Product Otoacoustic Emission Findings in Behçet’s Disease and Rheumatoid Arthritis

Abstract: Background and Objective: This study aimed to assess cochlear functions in Behçet’s disease and rheumatoid arthritis (RA) using otoacoustic emission testing (OAE), which objectively assesses outer hair cells in the cochlea. Methods: Patients with Behçet’s disease (n = 16) and RA (n = 11) as well as 20 controls were tested using pure tone audiometry and transiently evoked (TEOAEs) and distortion product OAEs (DPOAEs). Results: Pure tone results in the Behçet’s group were not significantly different from control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…The inner ear can be the target of autoimmune attack, and sensorineural hearing loss (SNHL) can occur as a complication in various non‐organ‐specific autoimmune diseases; however, the inner ear can also represent the primary focus of an autoimmune inner ear disease. Since the first description of autoimmune sensorineural hearing loss by McCabe in 1979, many studies have been published about hearing in autoimmune diseases such as rheumatoid arthritis, ankylosing spondylitis, Behçet disease, Sjögren syndrome, polyarteritis nodosa and systemic lupus erytematosus . However studies on high‐frequency hearing loss (HFHL) in psoriasis have been very limited.…”
mentioning
confidence: 99%
“…The inner ear can be the target of autoimmune attack, and sensorineural hearing loss (SNHL) can occur as a complication in various non‐organ‐specific autoimmune diseases; however, the inner ear can also represent the primary focus of an autoimmune inner ear disease. Since the first description of autoimmune sensorineural hearing loss by McCabe in 1979, many studies have been published about hearing in autoimmune diseases such as rheumatoid arthritis, ankylosing spondylitis, Behçet disease, Sjögren syndrome, polyarteritis nodosa and systemic lupus erytematosus . However studies on high‐frequency hearing loss (HFHL) in psoriasis have been very limited.…”
mentioning
confidence: 99%
“…Distortion product of otoacoustic emissions in RA patients were similar to control [9,11]. Acoustic reflexes were with normal thresholds, but with occasional prolonged latency.…”
Section: Discussionmentioning
confidence: 52%
“…It may be due to vasculitis, ossicular involvement, neuritis or ototoxicity of the drugs used for the treatment of rheumatologic diseases (18). Thus, hearing loss may be seen in conductive, sensorineural or in mixed pattern in secondary AIED (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20). Özcan et al suggested middle ear involvement for the reason of hearing loss in RA (18).…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte, otoakustik emisyon (OAE) gibi diğer testleri de içeren ve daha büyük örneklem büyüklüğüne sahip başka çalışmalara da ihtiyaç vardır. (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The inner ear pathologies caused by these disorders are commonly mild and slowly progressive whereas primary AIED is characterized by sudden onset, commonly bilateral, fluctuant and progressive sensorineural hearing loss (SNHL) with accompanying vertigo in some occasions.…”
Section: öZetunclassified